VERIFICATION OF IEEE STANDARDS 929-2000 AND 1547-2003 TO A SMALL PHOTOVOLTAIC SYSTEM CONNECTED TO BEER ELABD DISTRIBUTION GRID-NORTH SINAI-EGYPT - Rabea S. Selmy, Ahmed A. Daoud, Kamel A. Elserafy (Journal of engineering sciences and information technology, 2017)
This paper studied the power quality of grid connected photovoltaic (PV) system by verification of IEEE standards 929-2000 and 1547-2003 for a small PV system connected to a grid. For practical considerations, the PV system data extracted from a real standalone PV system and the distribution grid is simulated based on real data extracted from North Sinai distribution network. The Suggested system is simulated under different climate conditions to get real simulation of solar irradiation. A 10 KW grid connected PV system is modeled and simulated by using Matlab/Simulink software and the power quality parameters are studied under different levels of irradiance for the proposed system according to IEEE standards. System operated under normal and abnormal utility conditions. Results show a good compatibility with IEEE standards for subsystem proposed system in case of normal utility operation. In case of abnormal utility conditions, the PV system must island for protection issues.